2020
DOI: 10.1016/j.clnu.2019.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of body mass index and waist circumference before the onset of diabetes among people with prediabetes

Abstract: Background & aims: To investigate trajectories of body mass index (BMI) and waist circumference (WC) among prediabetic people who progressed to diabetes, people who remained with prediabetes, and those who returned to normoglycemia. Methods: We used data from 22,945 prediabetic people who received an annual health checkup for up to eight years. The development of diabetes was defined using the American Diabetes Association criteria. People who did not progress to diabetes during the observation period were cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
5
9
0
Order By: Relevance
“…Hence, decreasing WC and thus abdominal obesity could favour T2DM control. Indeed, in our study, participants who lost > 5 cm WC during follow-up were three times more likely to be controlled, although this association was not observed with HbA 1 c. A similar finding was reported in a Japanese study, where obese participants with prediabetes who lost WC returned to normoglycaemia ( Hu et al, 2019 ). Overall, our results suggest that decreasing WC might be beneficial for T2DM management.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Hence, decreasing WC and thus abdominal obesity could favour T2DM control. Indeed, in our study, participants who lost > 5 cm WC during follow-up were three times more likely to be controlled, although this association was not observed with HbA 1 c. A similar finding was reported in a Japanese study, where obese participants with prediabetes who lost WC returned to normoglycaemia ( Hu et al, 2019 ). Overall, our results suggest that decreasing WC might be beneficial for T2DM management.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings are in agreement with other studies, where increasing WC was found among subjects with T2DM ( De Backer et al, 2016 ). Increased WC has been shown to be a major determinant of T2DM incidence ( Hu et al, 2019 , Jeon et al, 2019 ) and control ( Hameed and AbdulQahar, 2019 , Mamo et al, 2019 ). Hence, decreasing WC and thus abdominal obesity could favour T2DM control.…”
Section: Discussionmentioning
confidence: 99%
“…Third, most of the studies did not consider the effects of additional confounders on the association between hearing loss and stroke. As a result, in this study, the role of smoking 53 , 54 , obesity 55 , physical activity 56 , occupational and environmental exposures such as shift work and noise, air pollution, all being associated with both stroke and hearing loss, has not been addressed. Fourth, most of the included cohort studies had a retrospective method.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical and epidemiologic studies have demonstrated that type 2 diabetes mellitus (T2DM) is correlated with obesity and blood pressure (BP) (12)(13)(14)(15)(16)(17). In addition to the absolute level of these risk factors, increasing evidence indicates that their longitudinal growth trajectory also plays a considerable role in the incident T2DM (18)(19)(20)(21)(22). However, most previous studies focused on the body mass index (BMI) and/or systolic BP in a single measurement or only paid attention to the association between the trajectories of BMI and incident diabetes, ignoring the dynamic trends of SBP in the life course.…”
Section: Introductionmentioning
confidence: 99%